Multimedia Research and Documentation of African Oral Genres: Reflections on Partnership [Presentation file]. - (:unkn) unknown (My University, 2010)
This paper presents the project Multimedia Research and Documentation of African Oral Genres: Connecting Diasporas and Local Audiences that focuses on multimedia as a tool for ‘sharing’ documentation and scientific knowledge with the cultural owners of the collected oral genres. The increasing number of African websites are further augmented by sites created outside of Africa by individuals in the diaspora, who nevertheless remain closely connected to their homeland communities. These tendencies indicate that electronic tools can be used to share documentation and research with local publics within Africa and with diasporic communities outside. ‘Sharing knowledge’, however, involves theoretical and methodological challenges. In particular, the practice and theory of academic partnership needs to be thoroughly interrogated when we consider the tensions that traverse the scientific endeavour on the cooperation between researchers, technicians and people from local communities. Our project suggests that scholars be more aware of the complex nature of their responsibility with regard to storytellers, audience(s) and their three-sided interaction, both scientifically and ethically, than has been previously advocated and attempted.
Keywords: African Research